Divided Mastery Slave Hiring in the American South - Martin, Jonathan D. (Harvard University Press, 2021)
Divided Mastery explores a curiously neglected aspect of the history of American slavery: the rental of slaves. Though few slaves escaped being rented out at some point in their lives, this is the first book to describe the practice, and its effects on both slaves and the peculiar institution. Martin reveals how the unique triangularity of slave hiring created slaves with two masters, thus transforming the customary polarity of master-slave relationships. Drawing upon slaveholders' letters, slave narratives, interviews with former slaves, legislative petitions, and court records, Divided Mastery ultimately reveals that slave hiring's significance was paradoxical. The practice bolstered the system of slavery by facilitating its spread into the western territories, by democratizing access to slave labor, and by promoting both production and speculation with slave capital.